An Analysis of the Convergence Problem of a Function in Functional Norms by Applying the Generalized Nörlund-Matrix Product Operator - Hari M. Srivastava; Hare K. Nigam; Swagata Nandy (Sci, 2023)
In this paper, we analyze the convergence problems of function g of Fourier series in Besov and generalized Zygmund norms using generalized Nörlund-Matrix (<semantics>Np,qA</semantics>) means of Fourier series. Convergence results are also compared by means of applications.